2009
DOI: 10.2308/accr.2009.84.5.1575
|View full text |Cite
|
Sign up to set email alerts
|

Management Forecasts in Japan: An Empirical Study of Forecasts that Are Effectively Mandated

Abstract: We study management forecasts in Japan, where forecasts are effectively mandated but managers have considerable latitude over the numbers they release. We find that managers' initial earnings forecasts for a fiscal year are systematically upward-biased but that they revise their forecasts downward during the fiscal year so that most earnings surprises are non-negative. Managers' initial forecast optimism is inversely related to firm performance, and is more pronounced for firms with higher levels of insider ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(181 citation statements)
references
References 30 publications
12
163
1
Order By: Relevance
“…While their sample might contain MFs disclosed for materiality reasons, this does not confound their tests or inferences. Other papers of a similar vein include: McNichols (1989), Williams (1996), Skinner (1997), Price (1999), Noe (1999), Hutton et al (2003), Ng et al (2007), Pevzner (2007), Hutton and Stocken (2009), and Kato et al (2009).…”
Section: Article In Pressmentioning
confidence: 94%
“…While their sample might contain MFs disclosed for materiality reasons, this does not confound their tests or inferences. Other papers of a similar vein include: McNichols (1989), Williams (1996), Skinner (1997), Price (1999), Noe (1999), Hutton et al (2003), Ng et al (2007), Pevzner (2007), Hutton and Stocken (2009), and Kato et al (2009).…”
Section: Article In Pressmentioning
confidence: 94%
“…Kato et al (2009) note that these management forecasts are 'effectively mandatory' for publicly-listed firms in Japan. In fact, 99.8% of firm years in our sample have management forecasts.…”
Section: (Ii) the Role Of Management Forecastsmentioning
confidence: 99%
“…In France, rules governing commission-sharing agreements (CSAs) were implemented by the Autorité des Marchés Financiers (AMF, the French Financial Markets Authority) in May 2007. In contrast to the GS, which addresses the conflicts of interest between financial research 1 A persistent optimism bias has also been observed in management forecasts by Japanese firms (Kato et al, 2009, Cho et al, 2011.…”
Section: Introductionmentioning
confidence: 98%